Wealth after work Planning your great escape - Harrison Debbie (Edinburgh, London Pearson education limited, 2002)
This publication is designed to provide accurate and authoritative information in regards to sound financial planning which is crucial for wealth after work. A future retirement of freedom and financial security involves some of the biggest financial decisions of ones life, so the need to be prepared, well informed and organized.
nmn, 03/08/16; oif 08/08/16
Loan
Keywords: Pension; Retirement planning; Finance, Personal